Distortion of Nepalese Culture and Social Norms in Upadhyay’s Buddha’s Orphans - Adhikary, Ramesh Prasad (ABC Journal of Advanced Research, 2020)
This research article is mainly focused on how Samrat Upadhyay has distorted Nepalese Culture and social norms in is novel Buddha’s Orphans. Nepalese culture and society are represented in a biased way from the western perspective. By using oriental stereotypes, the author has represented Nepal and the religious belief of Nepalese people in the wrong way. The characters of this novel like Bokey Ba, Kaki, Raja, Jamuna, and Ganga Da are presented as irrational and badly conservative people who believe in witch doctors, not in the medical doctors. They are presented as impulsive and eccentric. The setting of this novel is represented as exotic, inscrutable, and mysterious. Kathmandu valley and Nepalese people didn’t well describe as the real Kathmandu.  As a qualitative research, the researcher has taken the novel as a primary text and the concepts from orientalism, and the Foucauldian notion of representation is used as a tool to interpret the text. The researcher concluded that the novel is the misrepresentation of Nepalese culture and society.